SOSIALISASI PENGOLAHAN AIR GAMBUT MENJADI AIR MINUM DIDAERAH TALANG KERAMAT KABUPATEN BANYUASIN SUMATERA SELATAN - Muhammad Djoni Bustan; Sri Haryati; D Bahrin; Budi Santoso (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Peat water is identical with low acidity (pH), iron (Fe2+), manganese (Mn2+) and has a high color, making it difficult to treat it by filtering. From the results of batch and continuous processing using quicklime (CaO) and aluminum sulfate (Al2 (SO4)318 H2O) it was found that the levels of iron and manganese decreased significantly. For the batch process, iron decreased from 3.5 ppm to 0.1 ppm (97%), manganese from 0.59 ppm to 0 ppm (100%), color from 130 tcu to 1.7 tcu, while for turbidity there was a decrease from 33.8 ntu to 1.9 ntu, pH increased from 3.19 to 6.8. While in the continuous process with the same dose, iron decreased from 3.35 ppm to 0.05 ppm (98.6%), manganese from 0.5 ppm to 0 ppm (100%), pH increased from 3.19 to 7.16 while the turbidity of water decreased from 31.8 ntu to 1.14 ntu. The results of this peat water treatment meet the quality standard of the Minister of Health No. 32 of 2017. Based on the results of the research conducted, it is necessary to apply the results of the research that has been done to peat water in the Talang Sacred area and how processing technology and innovative products are processing peat water into drinkable water for peoples at Talang Keramat, Banyuasin Regency, South Sumatra